A method for degrading poly-L-lactic acid into L-lactide

By using an amino-bridged biaryloxy zinc complex catalyst, polyL-lactic acid is degraded to L-lactide under mild conditions, solving the problems of low catalytic activity and high reaction temperature in the prior art, and achieving efficient and selective lactide production.

CN119118988BActive Publication Date: 2025-04-04SUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411605422.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-04-04
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

In the prior art, when degrading polyL-lactic acid to L-lactide, there are problems such as low catalytic activity, high reaction temperature and low lactide separation yield.

Method used

The amino-bridged biaryloxy zinc complex is used as a catalyst to degrade polyL-lactic acid to L-lactide under conditions of 140~170°C. This method simplifies the separation process by sublimating the product under solvent-free conditions.

Benefits of technology

The efficient and selective degradation of polyL-lactic acid is achieved, the yield of lactide can reach 97%, the selectivity of L-lactide can reach 96%, and the degradation process is mild and the catalyst activity is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118988B_ABST
    Figure CN119118988B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of polymer degradation, and specifically relates to a method for degrading poly (L-lactic acid) to L-lactide. The present invention discloses a method for catalyzing the degradation of poly (L-lactic acid) to L-lactide under solvent-free and reduced pressure conditions using an amino-bridged bis-aryloxy zinc complex as a catalyst. The bis-aryloxy zinc complex used in the present invention has high catalytic activity, and the yield of the obtained lactide can reach up to 97%, wherein the stereoselectivity of L-lactide can reach 96%. The method has the advantages of simple catalyst synthesis steps, mild degradation reaction conditions, fast reaction rate, and high yield and selectivity of the obtained L-lactide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer degradation, and in particular relates to a method for degrading poly-L-lactic acid into L-lactide. Background Art

[0002] As a new type of biodegradable thermoplastic polymer material, poly (L-lactic acid) is increasingly replacing traditional petroleum-based polymer materials. The raw materials of poly (L-lactic acid) come from L-lactic acid in a series of natural crops such as corn and sweet potatoes. L-lactic acid is then polycondensed and thermally decomposed to obtain L-lactide. As a monomer of poly (L-lactic acid), L-lactide can be directly prepared from poly (L-lactic acid) through ring-opening polymerization. Materials prepared from poly (L-lactic acid) have been widely used in the fields of clothing, home appliance production, medical and health care, and information and communication due to their excellent biodegradability, strong physical and mechanical properties, and superior biocompatibility. Recycling poly (L-lactic acid) into L-lactide is of great significance in saving the cost of preparing poly (L-lactic acid) and promoting the green cycle of L-lactide.

[0003] The temperature required for direct degradation of poly (L-lactic acid) itself is greater than 350°C. The extremely high temperature leads to high energy consumption in the degradation process of poly (L-lactic acid) and poor selectivity of degradation products. In addition to lactide, a large number of oligomers are also produced (see: ICMcNeil, HA Leiper, Polym. Degrad. Stabil. 1985, 3, 267-285).

[0004] In order to solve these problems, introducing a suitable catalyst is an effective method. Noda's research group reported the catalytic performance of triisopropylaluminum, tetraisopropyltitanium, zinc chloride, zirconium oxide, stannous octoate and other catalysts, and found that stannous octoate can achieve the selective degradation of poly (L-lactic acid) at 230 ° C, with a lactide yield of 89% and a selectivity of L-lactide of 96% (see: M. Noda, H. Okuyama, Chem. Pharm. Bull. 1999, 47, 467-471).

[0005] Nishida's group reported the results of degradation of poly (L-lactic acid) catalyzed by CaO or MgO. The catalytic activity of CaO was better than that of MgO. Poly (L-lactic acid) began to degrade at 220°C and was completely degraded at 300°C. The yield of lactide reached 98% and the selectivity of L-lactide reached 80% (see: H. Nishida, T. Mori, T. Endo, Polymer 2004, 45, 1197-1205).

[0006] Enthaler's team used zinc acetate to catalyze the degradation reaction of poly (L-lactic acid). After 6 hours of reaction at 200 °C, the yield of lactide reached 98%, and the selectivity of L-lactide remained at 88% (see: E. Cheung, C. Alberti, S. Enthaler, ChemistryOpen 2020, 9, 1224-1228).

[0007] The Odelius group reported the degradation of poly (L-lactic acid) catalyzed by stannous octoate in the polar solvent N,N-dimethylformamide. The system showed excellent performance at 140 °C, with a selectivity of up to 99% for L-lactide. However, due to the presence of high-boiling-point solvents, high-temperature distillation is required to separate the product, and the separation yield of L-lactide is only 38% (see: L. Cederholm; J. Wohlert; P. Olsen; M. Hakkarainen; K. Odelius, Angew.Chem. Int. Ed. 2022, 61, e202204531).

[0008] Byers reported the results of the degradation of poly (L-lactic acid) catalyzed by a combination of zinc chloride and polyethylene glycol (molar ratio 1:2). At 160 °C, poly (L-lactic acid) can be completely degraded in 16 hours, with a yield of 98% and a selectivity of 99% (see: CF Gallin, W. Lee, JA Byers, Angew. Chem. Int. Ed. 2023, 62, e202303762).

[0009] Williams reported the results of degradation of poly (L-lactic acid) using a combination of stannous octoate and polyoxyethyl glycerol ether (molar ratio 1:80) as a catalyst. The reaction temperature was 160 ° C, the reaction time was 5 hours, and the yield of lactide obtained was 92%, with a selectivity of 99% (see: TM McGuire, A. Buchard, CK Williams, J. Am. Chem. Soc. 2023, 145, 19840).

[0010] Based on the above literature reports, it can be seen that the highly selective degradation of poly (L-lactic acid) to L-lactide still faces some problems, such as low catalytic activity, high reaction temperature, low lactide separation yield, etc. It is very meaningful to develop suitable catalysts to achieve efficient and highly selective degradation of poly (L-lactic acid) to L-lactide under relatively mild conditions. Summary of the invention

[0011] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:

[0012] The present invention provides a method for catalyzing the degradation of poly (L-lactic acid) to L-lactide. The present invention uses an amino-bridged bis-aryloxy zinc complex as a catalyst, and can degrade poly (L-lactic acid) to L-lactide at 140-170°C. The depolymerization reaction conditions are mild, the catalyst has high activity, the lactide yield can reach 97%, and the L-lactide selectivity can reach 96%. Under solvent-free conditions, L-lactide is separated by a sublimation method, which has great practical application prospects for the recycling of L-lactide.

[0013] The present invention provides a method for degrading poly (L-lactic acid) into L-lactide, comprising the following steps:

[0014] S1: Under the protection of an inert gas, dissolving poly (L-lactic acid) and a catalyst in a solvent, and removing the solvent under reduced pressure to obtain a solid mixture; the catalyst is selected from an amino-bridged bis-aryloxy zinc complex;

[0015] S2: heating the solid mixture to react under reduced pressure to separate and obtain L-lactide.

[0016] Preferably, the amino-bridged bis-aryloxy zinc complex is selected from one of structures ag:

[0017] .

[0018] Furthermore, the amino-bridged bis-aryloxy zinc complex is selected from structure b:

[0019] .

[0020] Preferably, the inert gas is nitrogen or argon.

[0021] Preferably, the molar ratio of the catalyst to poly (L-lactic acid) is 1:10-100.

[0022] Furthermore, the molar ratio of the catalyst to poly (L-lactic acid) is 1:20-40.

[0023] Preferably, the solvent is selected from one or more of dichloromethane, tetrahydrofuran, chloroform and toluene.

[0024] Preferably, the temperature of the heating reaction is 140-170°C.

[0025] Furthermore, the temperature of the heating reaction is 160°C.

[0026] Preferably, the pressure of the heating reaction is 0.67-5.74 mbar.

[0027] Furthermore, the pressure of the heating reaction is 0.67 mbar.

[0028] Preferably, the heating reaction time is 30-180 min.

[0029] Furthermore, the heating reaction time is 60 min.

[0030] Preferably, the molecular weight of the poly (L-lactic acid) is 20-65 kg / mol.

[0031] The technical solution of the present invention has the following advantages over the prior art:

[0032] The catalyst preparation is simple and has a high yield, the degradation process requires a low temperature and a fast reaction rate, the yield and selectivity of the product L-lactide are high, and the method of separating the product by sublimation is simple and effective. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the H-NMR spectrum of L-lactide obtained in Example 1 of the present invention.

[0034] Figure 2 for Figure 1 H NMR Figure 1 .60-1.80 ppm zoomed in; meso-lactide is meso-D,L-lactide.

[0035] Figure 3 This is the H-NMR spectrum of L-lactide obtained in Example 2 of the present invention.

[0036] Figure 4 This is the H-NMR spectrum of L-lactide obtained in Example 3 of the present invention.

[0037] Figure 5 This is the H-NMR spectrum of L-lactide obtained in Example 4 of the present invention.

[0038] Figure 6 This is the H-NMR spectrum of L-lactide obtained in Example 5 of the present invention.

[0039] Figure 7 This is the H-NMR spectrum of L-lactide obtained in Example 6 of the present invention.

[0040] Figure 8 This is the H-NMR spectrum of L-lactide obtained in Example 7 of the present invention.

[0041] Fig. 9 This is the H-NMR spectrum of L-lactide obtained in Example 8 of the present invention.

[0042] Fig.10This is the H-NMR spectrum of L-lactide obtained in Example 11 of the present invention.

[0043] Fig.11 This is the H-NMR spectrum of L-lactide obtained in Example 12 of the present invention.

[0044] Fig.12 This is the H-NMR spectrum of L-lactide obtained in Example 15 of the present invention.

[0045] Fig.13 This is the H-NMR spectrum of L-lactide obtained in Example 16 of the present invention.

[0046] Fig.14 It is the chemical reaction formula of the present invention.

[0047] Fig.15 is the H NMR spectrum of complex a; Fig.16 is the NMR carbon spectrum of complex a; Fig.17 is the H NMR spectrum of complex b; Fig.18 is the NMR carbon spectrum of complex b; Fig.19 is the H NMR spectrum of complex c; Fig. 20 is the NMR carbon spectrum of complex c; Fig.21 is the H NMR spectrum of complex d; Fig. 22 is the NMR carbon spectrum of complex d; Fig.23 is the H NMR spectrum of complex e; Fig.24 is the NMR carbon spectrum of complex e; Fig.25 is the H NMR spectrum of complex f; Fig.26 is the NMR carbon spectrum of complex f; Fig. 27 is the H NMR spectrum of complex g; Fig.28 is the NMR carbon spectrum of complex g. DETAILED DESCRIPTION

[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0049] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0050] In the following examples of the present invention, the catalyst used is an amino-bridged bis-aryloxy zinc complex, and their structural formula is as follows:

[0051] .

[0052] 1. Synthesis of complex a

[0053] 2,4-Dicumylphenol (16.52 g, 50 mmol), N,N-dimethylethylenediamine (2.64 g, 30 mmmol), and paraformaldehyde (0.6 g, 20 mmol) were placed in a round-bottom flask, and 30 mL of anhydrous methanol was added. The mixture was reacted at 80 °C for 1 day. The reaction mixture was cooled to room temperature to obtain a large amount of light yellow solid. 11.59 g of white powder L was isolated by vacuum filtration. 1 H 2 , yield 60%. Weigh L in a glove box 1 H 2 (2.31 g, 3 mmol) was added to the reaction flask, and then 10 mL of toluene was added. The reaction flask was removed from the glove box, placed in an ice-water bath, and ZnEt was slowly added dropwise. 2 The mixture was reacted at 50°C for 5 hours. After the reaction was cooled to room temperature, the solvent was drained and toluene (5 mL) was added to dissolve the solid. The solution was allowed to stand at 0°C to precipitate colorless crystals. The separated colorless crystals were washed with a small amount of toluene to obtain 1.81 g of white powder with a yield of 73%.

[0054] 2. Synthesis of complex b

[0055] 2,4-Di-tert-butylphenol (10.32 g, 50 mmol) was used to replace 2,4-dicumylphenol and the reaction mixture was prepared according to the method of synthesizing L 1 H 2 Synthesis method of L 2 H 2 10.49 g of white powder was obtained with a yield of 80%. 2 H 2 (1.57 g, 3 mmol) was added to the reaction flask, and then 10 mL of toluene was added. The reaction flask was removed from the glove box, placed in an ice water bath, and ZnEt was slowly added dropwise. 2 The mixture was reacted at 50 °C for 5 hours. After the reaction was cooled to room temperature, the solvent was drained and toluene (5 mL) was added to dissolve the solid. The solution was placed at 0 °C to precipitate colorless crystals. The separated colorless crystals were washed with a small amount of toluene to obtain 1.59 g of white powder with a yield of 90%.

[0056] 3. Synthesis of complex c

[0057] 3-tert-butyl-4-hydroxyanisole (9.01 g, 50 mmol) was used to replace 2,4-dicumylphenol and the reaction mixture was prepared according to the method of synthesizing L 1 H 2 Synthesis method of L 3 H 2 , 6.30 g of white powder was obtained with a yield of 80%. 3 H 2 (1.42 g, 3 mmol) was added to the reaction bottle, and then 10 mL of tetrahydrofuran was added. The reaction bottle was removed from the glove box, placed in an ice water bath, and ZnEt was slowly added dropwise. 2 The mixture was reacted at 50 °C for 5 hours. After the reaction was cooled to room temperature, the solvent was drained and tetrahydrofuran (5 mL) was added to dissolve the solid. The solution was placed at 0 °C to precipitate colorless crystals. The separated colorless crystals were washed with a small amount of tetrahydrofuran to obtain 1.37 g of white powder with a yield of 85%.

[0058] 4. Synthesis of complex d

[0059] 2-tert-Butyl-p-cresol (8.21 g, 50 mmol) was used to replace 2,4-dicumylphenol and the reaction mixture was prepared according to the method of synthesizing L 1 H 2 Synthesis method of L 4 H 2 7.16 g of white powder was obtained with a yield of 65%. 4 H 2 (1.32 g, 3 mmol) was added to the reaction flask, and then 10 mL of tetrahydrofuran was added. The reaction flask was removed from the glove box, placed in an ice-water bath, and ZnEt was slowly added dropwise. 2 The mixture was reacted at 50 °C for 5 hours. After the reaction was cooled to room temperature, the solvent was drained and tetrahydrofuran (5 mL) was added to dissolve the solid. The solution was placed at 0 °C to precipitate colorless crystals. The separated colorless crystals were washed with a small amount of tetrahydrofuran to obtain 1.28 g of white powder with a yield of 85%.

[0060] 5. Synthesis of complex e

[0061] Add p-chlorophenol (6.45 g, 50 mmol) and tert-butyl alcohol (9.68 mL, 100 mmol) to a flask, slowly add concentrated sulfuric acid (7 mL) under ice bath conditions, and react at room temperature for 1 day. After the reaction, pour the resulting mixture into ice water and extract with ethyl acetate (3 × 35 mL). Combine the organic phases and wash the organic phases with dilute hydrochloric acid until neutral. Use ethyl acetate and petroleum ether as developing solvents (ethyl acetate: petroleum ether = 1:4) and separate by silica gel column chromatography to obtain 2.39 g of yellow oily 2-tert-butyl-4-chlorophenol with a yield of 32%.

[0062] 2-tert-butyl-4-chlorophenol (7.47 g, 50 mmol) was used to replace 2,4-dicumylphenol and the reaction mixture was prepared according to the method of synthesizing L 1 H 2 Synthesis method of L 5 H 2 , 6.51 g of white powder was obtained with a yield of 65%. 5 H 2 (1.44 g, 3 mmol) was added to the reaction flask, and then 10 mL of toluene was added. The reaction flask was removed from the glove box, placed in an ice-water bath, and ZnEt was slowly added dropwise. 2 The mixture was reacted at 50 °C for 5 hours. After the reaction was cooled to room temperature, the solvent was drained and toluene (5 mL) was added to dissolve the solid. The solution was allowed to stand at 0 °C to precipitate colorless crystals. The separated colorless crystals were washed with a small amount of toluene to obtain 0.98 g of white powder with a yield of 60%.

[0063] 6. Synthesis of complex f

[0064] Substituting N,N-diisopropylethylenediamine (4.32 g, 30 mmol) for N,N-dimethylethylenediamine, the reaction mixture was prepared according to the method of synthesizing L 2 H 2 Synthesis method of L 6 H 2 10.89 g of white powder was obtained with a yield of 75%. 6 H 2 (1.74 g, 3 mmol) was added to the reaction flask, and then 10 mL of toluene was added. The reaction flask was removed from the glove box and placed in an ice-water bath. ZnEt was slowly added dropwise 2The mixture was reacted at 50 °C for 5 hours. After the reaction was cooled to room temperature, the solvent was drained and toluene (5 mL) was added to dissolve the solid. The solution was placed at 0 °C to precipitate colorless crystals. The separated colorless crystals were washed with a small amount of toluene to obtain 1.74 g of white powder with a yield of 90%.

[0065] 7. Synthesis of complex g

[0066] Substituting 2-methoxyethylamine (2.25 g, 30 mmol) for N,N-dimethylethylenediamine, the reaction mixture was prepared according to the method of synthesizing L 2 H 2 Synthesis method of L 7 H 2 8.96 g of white solid was obtained with a yield of 70%. 7 H 2 (1.54 g, 3 mmol) was added to the reaction bottle, and then 10 mL of tetrahydrofuran was added. The reaction bottle was removed from the glove box, placed in an ice water bath, and ZnEt was slowly added dropwise. 2 The mixture was reacted at 50 °C for 5 hours. After the reaction was cooled to room temperature, the solvent was drained and tetrahydrofuran (5 mL) was added to dissolve the solid. The solution was placed at 0 °C to precipitate colorless crystals. The separated colorless crystals were washed with a small amount of tetrahydrofuran to obtain 1.21 g of white powder with a yield of 70%.

[0067] Example 1 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:35) at 160 °C and 0.67 mbar to produce L-lactide

[0068] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0176 g of zinc complex b (0.03 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C and maintained under reduced pressure of 0.67 mbar for 1 hour. Finally, lactide (0.1397 g, yield 97%) was obtained in the collection tube, and the collected lactide was characterized by nuclear magnetic hydrogen spectrum, where the selectivity of L-lactide was 96%.

[0069] Example 2 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:10) at 160 °C and 0.67 mbar to produce L-lactide

[0070] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0588 g of zinc complex b (0.1 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 0.4 hours. Finally, lactide (0.1411 g, yield 98%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0071] Example 3 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:12.5) at 160 °C and 0.67 mbar to produce L-lactide

[0072] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0471 g of zinc complex b (0.08 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected with a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 0.5 hours. Finally, lactide (0.1411 g, yield 98%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0073] Example 4 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:20) at 160 °C and 0.67 mbar to produce L-lactide

[0074] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0294 g of zinc complex b (0.05 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 0.72 hours. Finally, lactide (0.1397 g, yield 97%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0075] Example 5 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:100) at 160 °C and 0.67 mbar to produce L-lactide

[0076] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0059 g of zinc complex b (0.01 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected with a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 1.5 hours. Finally, lactide (0.0489 g, yield 34%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0077] Example 6 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:35) at 170 °C and 0.67 mbar to produce L-lactide

[0078] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0176 g of zinc complex b (0.03 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected with a latex tube, and the reaction bottle was placed in an oil bath at 170 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 0.5 hours. Finally, lactide (0.1397 g, yield 97%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 98%.

[0079] Example 7 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:35) at 150 °C and 0.67 mbar to produce L-lactide

[0080] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0176 g of zinc complex b (0.03 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 150 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 3 hours. Finally, lactide (0.1296 g, yield 90%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0081] Example 8 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:35) at 140 °C and 0.67 mbar to produce L-lactide

[0082] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0176 g of zinc complex b (0.03 mmol) was added, and they were dissolved in 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 140 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 3 hours. Finally, lactide (0.0605 g, yield 42%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0083] Example 9 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:35) at 160 °C and 1.77 mbar to produce L-lactide

[0084] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0176 g of zinc complex b (0.03 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected with a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 1.77 mbar for 1 hour. Finally, lactide (0.1339 g, yield 93%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0085] Example 10 Zinc complex b catalyzes the degradation of poly (L-lactic acid) (1:35) at 160 °C and 5.74 mbar to produce L-lactide

[0086] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0176 g of zinc complex b (0.03 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C and maintained under reduced pressure of 5.74 mbar for 1 hour. Finally, lactide (0.1253 g, yield 87%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 92%.

[0087] Example 11 Zinc complex a catalyzes the degradation of poly (L-lactic acid) (1:35) at 160 °C and 0.67 mbar to produce L-lactide

[0088] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0251 g of zinc complex a (0.03 mmol) was added, and they were dissolved in 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C and maintained under reduced pressure of 0.67 mbar for 1 hour. Finally, lactide (0.1051 g, yield 73%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 98%.

[0089] Example 12 Zinc complex c catalyzes the degradation of poly (L-lactic acid) (1:35) at 160 °C and 0.67 mbar to produce L-lactide

[0090] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0161 g of zinc complex c (0.03 mmol) was added, and they were dissolved with 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected with a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 1 hour. Finally, lactide (0.0994 g, yield 69%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0091] Example 13 Zinc complex d catalyzes the degradation of poly (L-lactic acid) (1:35) at 160 °C and 0.67 mbar to produce L-lactide

[0092] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0151 g of zinc complex d (0.03 mmol) was added, and they were dissolved in 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 1 hour. Finally, lactide (0.1037 g, yield 72%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0093] Example 14 Zinc complex e catalyzes the degradation of poly (L-lactic acid) (1:35) at 160 °C and 0.67 mbar to produce L-lactide

[0094] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0163 g of zinc complex e (0.03 mmol) was added, and they were dissolved in 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 1 hour. Finally, lactide (0.0518 g, yield 36%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 94%.

[0095] Example 15 Zinc complex f catalyzes the degradation of poly (L-lactic acid) (1:35) at 160 °C and 0.67 mbar to produce L-lactide

[0096] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0193 g of zinc complex f (0.03 mmol) was added, and they were dissolved in 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 1 hour. Finally, lactide (0.1296 g, yield 90%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 95%.

[0097] Example 16 Zinc complex g catalyzes the degradation of poly (L-lactic acid) (1:35) at 160 °C and 0.67 mbar to produce L-lactide

[0098] In a glove box protected by high-purity nitrogen, 0.1440 g of poly-L-lactic acid (1 mmol) was added to the reaction bottle, and then 0.0172 g of zinc complex g (0.03 mmol) was added, and they were dissolved in 1 mL of anhydrous dichloromethane to obtain a colorless solution. The dichloromethane was slowly removed under reduced pressure to obtain a thin film of the mixture. The reaction bottle and the collection tube were connected using a latex tube, and the reaction bottle was placed in an oil bath at 160 ° C. The reaction was maintained under reduced pressure of 0.67 mbar for 1 hour. Finally, lactide (0.0763 g, yield 53%) was obtained in the collection tube. The collected lactide was characterized by nuclear magnetic hydrogen spectrum, and the selectivity of L-lactide was 96%.

[0099] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for degrading poly (L-lactic acid) into L-lactide, characterized in that: The steps include: S1: Under the protection of an inert gas, dissolving poly (L-lactic acid) and a catalyst in a solvent, and removing the solvent under reduced pressure to obtain a solid mixture; the catalyst is selected from an amino-bridged bis-aryloxy zinc complex; S2: heating the solid mixture under reduced pressure to react and separating L-lactide; the amino-bridged bis-aryloxy zinc complex is selected from one of structures ag: 。 2. The method for degrading poly (L-lactic acid) into L-lactide according to claim 1, characterized in that: The amino-bridged bis-aryloxy zinc complex is selected from structure b: 。 3. The method for degrading poly (L-lactic acid) into L-lactide according to claim 1, characterized in that: The inert gas is nitrogen or argon.

4. The method for degrading poly (L-lactic acid) into L-lactide according to claim 1, characterized in that: The molar ratio of the catalyst to poly (L-lactic acid) is 1:10-100.

5. The method for degrading poly (L-lactic acid) into L-lactide according to claim 1, characterized in that: The solvent is selected from one or more of dichloromethane, tetrahydrofuran, chloroform and toluene.

6. The method for degrading poly (L-lactic acid) into L-lactide according to claim 1, characterized in that: The temperature of the heating reaction is 140-170°C.

7. The method for degrading poly (L-lactic acid) into L-lactide according to claim 1, characterized in that: The pressure of the heating reaction is 0.67-5.74 mbar.

8. The method for degrading poly (L-lactic acid) into L-lactide according to claim 1, characterized in that: The heating reaction time is 30-180 min.

9. The method for degrading poly (L-lactic acid) into L-lactide according to claim 1, characterized in that: The molecular weight of the poly-L-lactic acid is 20-65 kg / mol.

Citation Information

Patent Citations

  • Magnesium catalyst and method for recovering racemic lactide by depolymerizing high-regularity polylactic acid

    CN115073418A

  • Zinc catalyst and method for recovering racemic lactide by depolymerizing polylactic acid stereocomplex

    CN115160287A